Evaluations of elephant grass cultivars in two physiographic regions of Minas Gerais state, Brazil - Botrel, Milton de Andrade; Alvim, Maurílio José (Pesquisa Agropecuaria Brasileira, 1992)
The cultivars Mineiro, Taiwan A-146, Cameroon and Kizozi of elephant grass were evaluated in the South and Campos das Vertentes regions of Minas Gerais State, in a randomized complete block design with 3 replicates, monthly forage production rate (MFPR), stem : leaves ratio (S/L), tiller number (TN) and grass protein content (GPC) were measured either in the dry or in the rainy season. In the South region, cv. Taiwan A-146, and Mineiro exhibited the highest MFPR in both dry and rainy season, whereas the lowest yield was shown by cv. Kizozi. In the Campos das Vertentes region, the best MFRP results were obtained with cv. Mineiro in the dry season. The smallest S/L was shown by cv. Cameroon. No differences among cultivars were found regarding GPC. TN, in turn, was the highest in cv. Cameroon; no other significant contrast was found.